The Role of Heart Rate Variability in the Future of Remote Digital Biomarkers - Owens, Andrew P. (Frontiers in Neuroscience, 2020)
Heart rate variability (HRV) offers insights into humoral, neural and autonomic nervous system neurovisceral processes in health and disorders of brain, body and behaviour but has yet to be fully potentiated in the digital age. Remote measurement technologies (RMTs), such as, smartphones, wearable sensors or home-based devices, can passively capture HRV as a nested parameter of neurovisceral integration and health during everyday life, providing detailed insights across different contexts, such as activities of daily living, therapeutic interventions and behavioural tasks, to compliment ongoing clinical care. Many RMTs measure HRV, even consumer wearables and smartphones, which can be deployed as wearable sensors or digital cameras using photoplethysmography. RMTs that measure HRV provide the opportunity to identify sensitive and optimised digital biomarkers indicative of changes in health or disease status in disorders where neurovisceral processes are compromised. The sympathetic and parasympathetic nervous systems are affected differently in different disorders, treatments and contexts and RMT-based HRV therefore has significant potential as an adjunct digital biomarker in neurovisceral digital phenotyping that can add continuously updated, objective and relevant data to existing clinical methodologies, aiding the evolution of current ‘diagnose and treat’ care models to a more proactive and holistic approach that pairs established autonomic markers with advances in remote digital technology.